Degree of facial profile convexity using Subtelny’s analysis in patients aged 6 to 12 years - Dominique, Vanessa; Nofrizal, Riko (Majalah Kedokteran Gigi Indonesia, 2023)
Skeletal malocclusion is caused by a disproportion of the maxilla and mandible, which leads to an unharmonious facial profile. Straight, convex, and concave soft tissue profiles may serve as a guide to determine the underlying skeletal relations and location of the jaws from the anteroposterior plane. In this study, Subtelny’s cephalometric analysis of the skeletal and soft tissue profile is used to evaluate the facial profile convexity and is divided into three parts, which are the skeletal profile convexity, soft tissue profile convexity, and total soft tissue profile convexity. The purpose of this study is to determine the degree of facial profile convexity according to Subtelny’s analysis in patients aged 6 to 12 years at Faculty of Dentistry Dental Hospital of Trisakti University. This was a descriptive observational study using samples of cephalograms of 40 patients aged 6 to 12 years. Cephalometry tracing and identification of anatomical landmarks were done to acquire the facial profile convexity degrees. The anatomical landmarks used were nasion, A-point, pogonion, soft tissue nasion, subnasale, pronasale, and soft tissue pogonion. The results of this study found that the average degree of the skeletal profile convexity was 171.26°, the soft tissue profile convexity was 166.18°, and the total soft tissue profile convexity was 144.83°. The degrees of skeletal profile convexity, soft tissue profile convexity, and total soft tissue profile convexity could be influenced by age, gender, and differences in growth and changes in the skeletal and facial soft tissue structures.